Legal Protection for Consumers Against Unlabelled Processed Food Production in Keerom Regency, Papua Province - Herniati Herniati (PT. AVID MEDIA INDONESIA, 2026)
The circulation of unlabeled processed food remains a serious problem in Keerom Regency, Papua Province, particularly those produced by small-scale businesses and home industries. This situation has the potential to harm consumers due to the lack of clear information regarding composition, expiration dates, distribution permits, and producer identities, thus threatening consumer health and safety. This study aims to determine the form of legal protection for consumers against the production of unlabeled processed food in Keerom Regency and to identify the factors causing the continued circulation of unlabeled processed food. The research method used is a juridical-empirical legal research with a legislative approach and a sociological approach. Data were obtained through field research by conducting interviews with relevant agencies, business actors, and consumers, as well as library research through a review of relevant laws and legal literature. The results of the study indicate that legal protection for consumers against the production of unlabeled processed food in Keerom Regency has not been implemented optimally, which is caused by a lack of legal understanding of business actors, complicated licensing procedures, and weak supervision from the Food and Drug Monitoring Agency (BPOM).